Foreign direct investment and inequality in four ASEAN nations - Merican, Yasmine; Yusop, Zulkornain; Mohd. Noor, Zaleha; Law, Siong Hook (2007)
We tested the impact of foreign direct investment on inequality in Malaysia, Thailand, Indonesia, and the Philippines- significant FDI recipients amongst developing nations from 1970-2001. Our time-series analysis of the estimated gini coefficients, employing the Auto-regressive Distributive Lag (ARDL) technique suggest that FDI improves income inequality in Malaysia and Indonesia but worsens inequality in Thailand while it proved insignificant for the Philippines.